Advocating Journalism Practice-as-research: A Case for Recognition in the New Zealand PBRF Context. (June 2015) - Robie, David
New Zealand's Performance-Based Research Fund regime makes no explicit provision for journalism practice-as-research, although it does not exclude it either. The Tertiary Education Commission (TEC) has hinted at applied research changes that may open the door to investigative journalism and other long-form modes for the next audit in 2018. As a growing global debate responds to international pressure on journalism practitioner-academics to publish scholarly outputs and seek external research income, there has been a parallel paradigm shift in defining methodologies for some journalism as research. This article advocates a bolder approach by journalism educators in New Zealand to push the boundaries for greater acceptance of journalism research methodologies and to claim an enhanced academic space as a 'critic and conscience of society'.